Composite material as well as preparation method and application thereof

By using nitrogen and oxygen co-doped carbon nanocage-loaded iron trioxide composite materials in metal lithium batteries, the problems of unsatisfactory lithium deposition effect and high overpotentiality are solved, and the negative electrode material of metal lithium battery with low cost and good performance is achieved.

CN119673979APending Publication Date: 2025-03-21CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311213435.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing metal lithium anode materials have problems such as poor lithium deposition effect and high overpotential during charging and discharging, and the material preparation cost is relatively high.

Method used

The composite material with nitrogen and oxygen co-doped carbon nanocage as the carrier and the internally loaded iron trioxide is prepared through low-temperature pyrolysis and pickling steps, achieving the boundary directional growth of metal lithium.

Benefits of technology

The material has good lithium-philicity and a low lithium deposition overpotential, which reduces the cost of material preparation and does not require precious metals or polymer materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673979A_ABST
    Figure CN119673979A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nanocarbon composite materials, and discloses a composite material and a preparation method and application thereof.The composite material comprises a carrier and Fe2O3 nanoparticles filled in the carrier, and the carrier is a nitrogen-oxygen co-doped carbon nanocage; wherein in the composite material measured by X-ray photoelectron spectroscopy, the molar content of carbon element is 75-98%, the molar content of oxygen element is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%. The material has good lithium affinity and relatively low lithium deposition overpotential, and is beneficial to inducing metal lithium to enter a cage cavity for deposition. Precious metal or polymer materials are not needed, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano-carbon composite materials, and in particular to a composite material and a preparation method and application thereof. Background Art

[0002] Metal lithium anode has become an ideal anode material for the next generation of high energy density secondary batteries due to its extremely high theoretical specific capacity and lowest electrode potential. However, during the charge and discharge process, due to the host-free characteristics of metal lithium, it will cause volume expansion, rupture of the solid electrolyte membrane, low coulombic efficiency, poor cycle stability and poor safety during the cycle. Currently, most of the carrier materials used for metal lithium anodes use carbon materials as an effective skeleton for lithium deposition, but the metal lithium is still deposited on the surface of the skeleton, making it difficult to achieve confined directional growth of metal lithium, and unable to fundamentally solve the side reactions, volume expansion and lithium dendrite growth problems of metal lithium.

[0003] CN112447949A discloses a dual-lithium-philic composite lithium metal negative electrode active material, comprising a carbon hollow sphere and a lithium-philic precious metal nanoparticle composited on the inner wall of the carbon hollow sphere; the shell material of the carbon hollow sphere is a nitrogen-doped carbon material. The material has good lithium affinity and electronic conductivity, but the lithium metal negative electrode needs to introduce a precious metal single substance, which is relatively costly.

[0004] CN114335540A discloses a lithium-philic carbon skeleton composite material, which includes gold, salt containing gold, silver, salt containing silver, zinc, zinc oxide, salt containing zinc, silicon, silicon oxide, phosphorus, TiO2 and other lithium-philic materials loaded in the through holes of fibrous carbon nanomaterials, which can reduce the nucleation overpotential and optimize the lithium deposition site. However, it is still necessary to coat the skeleton with a polymer layer, otherwise the lithium metal is in direct contact with the electrolyte, there are more side reactions, and the first effect and cycle performance are poor, but the polymer layer will also weaken the lithium-philicity of the lithium-philic substance.

[0005] Therefore, although the above-mentioned metal lithium negative electrode can improve the lithium affinity of the carbon negative electrode to a certain extent, the lithium deposition effect is not ideal and the material preparation cost is relatively high. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of unsatisfactory lithium deposition effect and high overpotential of lithium metal negative electrode materials in the prior art, and to provide a composite material and a preparation method and application thereof, wherein the composite material has good lithium affinity and low lithium deposition overpotential.

[0007] In order to achieve the above object, the present invention provides a composite material in a first aspect, comprising a carrier and Fe2O3 nanoparticles filled in the carrier, wherein the carrier is a nitrogen-oxygen co-doped carbon nanocage;

[0008] The X-ray photoelectron spectroscopy measured that the molar content of carbon in the composite material was 75-98%, the molar content of oxygen was 1-10%, the molar content of nitrogen was 0.5-5%, and the molar content of iron was 0.5-10%.

[0009] Preferably, in the composite material, the molar ratio of oxygen to nitrogen is 5-15:1, preferably 5-10:1.

[0010] A second aspect of the present invention provides a method for preparing a composite material, comprising the following steps:

[0011] (1) providing a homogeneous solution containing a transition metal salt, a nitrogen-containing organic carboxylic acid and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid; and the mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.1-100;

[0012] (2) subjecting the precursor to low-temperature pyrolysis in an inert atmosphere and / or a reducing atmosphere to obtain a pyrolysis product; the temperature of the low-temperature pyrolysis is not higher than 650° C.;

[0013] (3) acid-washing the pyrolysis product, and then performing solid-liquid separation, washing and drying to obtain nitrogen-oxygen co-doped carbon nanocages;

[0014] (4) impregnating the nitrogen-oxygen co-doped carbon nanocage with an iron salt solution under vacuum conditions, and then performing a heat treatment;

[0015] (5) Under an oxygen-containing atmosphere, the product obtained in step (4) is passivated.

[0016] The third aspect of the present invention provides the use of the composite material or the composite material prepared by the above preparation method in a metal lithium battery.

[0017] The composite material provided by the present invention uses nitrogen-oxygen co-doped carbon nano cages as carriers, and the carbon cages are loaded with ferric oxide. The material has good lithium affinity and low lithium deposition overpotential, which is conducive to inducing metal lithium to enter the cage cavity for deposition. No precious metals or polymer materials are needed, and the cost is low.

[0018] The method provided by the present invention overcomes the problems of the prior art in which the metal organic framework structure precursor needs to be prepared by using a high temperature and high pressure reactor for self-assembly, a large amount of organic solvent is wasted, and the purification steps are cumbersome, and no polymer additive is required, thus simplifying the reaction steps. In addition, the present invention introduces metal oxides by a vacuum-filling method, without the need to introduce an exogenous template, which is conducive to reducing production costs and realizing large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1is the XRD pattern of the composite material A1 and the nitrogen-oxygen co-doped carbon nanocage prepared in Example 1;

[0020] Figure 2 is the XPS graph of the composite material prepared in Example 1;

[0021] Figure 3 is the XPS Fe 2p spectrum of the composite material prepared in Example 1;

[0022] Figure 4 is a TEM image of the composite material prepared in Example 1. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] In the present invention, the nitrogen-oxygen co-doped carbon nanocage has a hollow cage structure surrounded by nitrogen-oxygen co-doped graphitized carbon layers, and the graphitized carbon layer refers to a carbon structure with a layered structure that can be clearly observed under a high-resolution transmission electron microscope, rather than an amorphous structure.

[0025] In the present invention, the "nitrogen" and "oxygen" in the term "nitrogen-oxygen co-doped carbon nanocage" refer to nitrogen and oxygen elements, that is, nitrogen and oxygen elements in various forms formed in the graphitized carbon layer during the preparation of nitrogen-oxygen co-doped carbon nanocages. The "molar content of oxygen" is the total content of all forms of oxygen elements, and similarly, the "molar content of nitrogen" is the total content of all forms of nitrogen elements.

[0026] A first aspect of the present invention provides a composite material, comprising a carrier and Fe2O3 nanoparticles filled in the carrier, wherein the carrier is a nitrogen-oxygen co-doped carbon nanocage;

[0027] The X-ray photoelectron spectroscopy measured that the molar content of carbon in the composite material was 75-98%, the molar content of oxygen was 1-10%, the molar content of nitrogen was 0.5-5%, and the molar content of iron was 0.5-10%.

[0028] The composite material provided by the present invention uses nitrogen-oxygen co-doped carbon nano cages as carriers, and internally loads ferric oxide. The inventors of the present invention have found that the lithium affinity of the material can be improved, the lithium deposition overpotential can be reduced, and it is beneficial to induce metallic lithium to enter the cage cavity for deposition. The composite material does not contain precious metals or polymer materials, and has low cost.

[0029] Transmission electron microscopy (TEM) characterization shows that the composite material has a cage-like structure, and clear Fe2O3 lattice fringes can be seen in the cage, proving that Fe2O3 is contained in the carbon cage. At the same time, through X-ray photoelectron spectroscopy analysis and XRD testing, it can be determined that the iron element in the composite material exists in the form of Fe2O3.

[0030] According to some preferred embodiments of the present invention, the molar content of carbon in the composite material is 84-94%, the molar content of oxygen is 5-8%, the molar content of nitrogen is 0.5-3%, and the molar content of iron is 0.5-5% as measured by X-ray photoelectron spectroscopy.

[0031] It can be understood that when the composite material contains only carbon, oxygen, nitrogen and iron elements, the sum of the molar contents of each component satisfies 100%.

[0032] In the present invention, the X-ray photoelectron spectroscopy analysis was tested on an ESCALab250 X-ray photoelectron spectrometer equipped with ThermoAvantage V5.926 software from Thermo Scientific. The excitation source was monochromatic AlKα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis test was 6.53×10 -9 The electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon. The data were processed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module.

[0033] In the present invention, preferably, the molar ratio of oxygen to nitrogen in the composite material measured by X-ray photoelectron spectroscopy is 5-15:1, for example, it can be any one or two of 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1. By controlling the ratio of nitrogen and oxygen co-doping, it is more conducive to inducing metallic lithium to enter the carbon nanocage for deposition, uniformly depositing metallic lithium, and effectively inhibiting the growth of metallic lithium dendrites. Preferably, the molar ratio of oxygen to nitrogen is 5-10:1.

[0034] According to the present invention, preferably, the particle diameter of the composite material is 5-40 nm, preferably 5-30 nm, and more preferably 5-20 nm. The particles of the composite material have a small diameter and a large curvature, which is conducive to the transmission and deposition of metallic lithium.

[0035] Preferably, the thickness of the cage wall of the nitrogen and oxygen co-doped carbon nanocage in the composite material is 1-30 nm, preferably 1-10 nm, and more preferably 1-5 nm.

[0036] In the present invention, the surface morphology of the material is characterized by high-resolution transmission electron microscopy (HRTEM), the model of the high-resolution transmission electron microscope used is JEM-2100 (Japan Electron Co., Ltd.), and the high-resolution transmission electron microscope test conditions are: the acceleration voltage is 200kV. The diameter of the nitrogen-oxygen co-doped carbon nanocage and the thickness of the cage wall of the nitrogen-oxygen co-doped carbon nanocage can be measured by high-resolution transmission electron microscope images.

[0037] According to the present invention, preferably, the specific surface area of ​​the nitrogen and oxygen co-doped carbon nanocage is 50-1000m 2 / g, preferably 200-800m 2 / g, more preferably 300-600m 2 / g.

[0038] According to the present invention, the nitrogen-oxygen co-doped carbon nanocage has a loose and porous cage wall, which is conducive to the filling and deposition of metallic lithium. Preferably, the pore volume of the cage wall of the nitrogen-oxygen co-doped carbon nanocage is 0.5-1cm 3 / g, preferably 0.65-1cm 3 / g.

[0039] In the present invention, the pore structure properties of the material are detected by the BET test method, which is specifically measured using a Quantachrome AS-6B analyzer, and the BET specific surface area of ​​the material is obtained by the Brunauer-Emmett-Taller (BET) method.

[0040] A second aspect of the present invention provides a method for preparing a composite material, comprising the following steps:

[0041] (1) providing a homogeneous solution containing a transition metal salt, a nitrogen-containing organic carboxylic acid and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid; and the mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.1-100;

[0042] (2) subjecting the precursor to low-temperature pyrolysis in an inert atmosphere and / or a reducing atmosphere to obtain a pyrolysis product; the temperature of the low-temperature pyrolysis is not higher than 650° C.;

[0043] (3) acid-washing the pyrolysis product, and then performing solid-liquid separation, washing and drying to obtain nitrogen-oxygen co-doped carbon nanocages;

[0044] (4) impregnating the nitrogen-oxygen co-doped carbon nanocage with an iron salt solution under vacuum conditions, and then performing a heat treatment;

[0045] (5) Under an oxygen-containing atmosphere, the product obtained in step (4) is passivated.

[0046] In the present invention, a nitrogen-oxygen co-doped carbon nanocage carrier is first prepared, and then a vacuum impregnation method is used to introduce a metal oxide into the carrier. The present invention pyrolyzes a precursor prepared by reacting a transition metal salt and a nitrogen-containing organic carboxylic acid in a solvent at a relatively low temperature, and then obtains a nitrogen-oxygen co-doped carbon nanocage by acid washing. The obtained nitrogen-oxygen co-doped carbon nanocage has a relatively high oxygen content. It overcomes the problems of the prior art that the preparation of metal organic framework structure precursors requires the use of a high-temperature and high-pressure reactor for self-assembly, a large amount of organic solvents are wasted, and the purification steps are cumbersome, and no polymer additives are required, simplifying the reaction steps. In addition, the present invention adopts a vacuum-filling method to introduce metal oxides, and there is no need to introduce an exogenous template, which is conducive to large-scale production and has low cost.

[0047] According to the present invention, preferably, the mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.5-50, preferably 1:0.5-5.

[0048] The present invention has no particular limitation on the specific method of forming the homogeneous solution in step (1), for example, the homogeneous solution may be formed by heating, preferably by heating and stirring. The present invention also has no particular limitation on the heating temperature and stirring rate, as long as the homogeneous solution can be formed.

[0049] According to the present invention, preferably, the transition metal salt and the nitrogen-containing organic carboxylic acid are dissolved in a solvent to form a homogeneous solution. The present invention has no particular limitation on the type of the solvent, as long as a homogeneous solution can be formed. Preferably, the solvent is water and / or ethanol, more preferably water; the present invention has no particular limitation on the amount of the solvent, as long as a homogeneous solution can be formed.

[0050] In the present invention, the solvent in the homogeneous solution can be removed by existing techniques known to those skilled in the art, and the present invention has no particular limitation on this. For example, the solvent in the homogeneous solution can be removed by heating and evaporating to dryness.

[0051] In the present invention, there is no special limitation on the specific type of the transition metal salt. Preferably, the transition metal salt is selected from organic acid salts and / or inorganic salts of transition metals; preferably, the organic acid salt of the transition metal is an organic carboxylate free of heteroatoms, preferably acetate; preferably, the inorganic salt of the transition metal is at least one of transition metal halides, carbonates and basic carbonates.

[0052] In the present invention, preferably, the transition metal is a Group VIII metal and / or a Group IB metal, preferably at least one of iron, cobalt, nickel and copper, more preferably nickel.

[0053] According to the present invention, preferably, in step (2), the low-temperature pyrolysis conditions include: a heating rate of 0.5-30°C / min, preferably 1-10°C / min; a temperature of 350-450°C, preferably 350-400°C; for example, it can be a specific temperature of 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, or a temperature range between two points. Preferably, the constant temperature time is 20-600min, preferably 60-480min. In the prior art, in order to ensure that the carbon coating has a high degree of graphitization, the generally used calcination or heat treatment temperature is not less than 600°C. A higher degree of graphitization is conducive to improving the conductivity of the material, but the inventors of the present invention have found in their research that a lower calcination temperature can increase the oxygen content in the material. The synergistic effect of nitrogen-oxygen co-doped carbon nanocages and Fe2O3 nanoparticles loaded inside the carrier is conducive to improving lithium affinity and reducing lithium deposition overpotential.

[0054] In the present invention, preferably, in step (2), the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium.

[0055] Preferably, the reducing atmosphere is hydrogen.

[0056] In the present invention, in step (3), the acid washing peels off the transition metal to form a hollow cage-like structure. The specific operation process of the acid washing can adopt the existing technology known to those skilled in the art, and the present invention has no special limitation on this.

[0057] Preferably, the pickling comprises: mixing the pyrolysis product with a pickling agent. The present invention has no particular limitation on the specific manner of the mixing, and the mixing can be performed by ultrasound or stirring.

[0058] The pickling agent can be an acid or an acid aqueous solution conventional in the art. As long as the transition metal can be stripped. Preferably, the pickling agent is an inorganic acid aqueous solution and / or an organic acid aqueous solution, preferably at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a nitric acid aqueous solution and a citric acid aqueous solution, more preferably a hydrochloric acid aqueous solution. Preferably, the concentration of the inorganic acid aqueous solution or the organic acid aqueous solution is 0.5-2 mol / L. The present invention does not particularly limit the amount of the pickling agent, as long as the transition metal can be stripped, and those skilled in the art can choose according to actual conditions.

[0059] Preferably, in step (3), the pickling temperature is 20-110°C, preferably 60-90°C; the time is 0.1-48h, preferably 4-12h.

[0060] According to the present invention, in step (3), there is no particular limitation on the solid-liquid separation method, and the solid-liquid separation can be carried out by a solid-liquid separation method known in the art, for example, solid-liquid separation can be carried out by filtration, suction filtration, centrifugation, etc. The liquid obtained after solid-liquid separation can be reused as a raw material for preparing nitrogen-oxygen co-doped carbon nanocages.

[0061] Preferably, in step (3), the washing is used to remove the acid wash agent remaining on the nano-carbon material, and therefore, various water washing methods that can wash the nitrogen-oxygen co-doped carbon nanocage to neutrality are applicable to the present invention. The drying is used to remove water on the nitrogen-oxygen co-doped carbon nanocage. Drying can be carried out by normal pressure drying or reduced pressure drying, and the drying conditions can adopt any feasible existing technology, preferably, drying is carried out at 80-140°C.

[0062] In the present invention, the metal oxide is introduced by the vacuum-filling method without introducing an exogenous template, which is conducive to large-scale production and has low cost.

[0063] According to the present invention, preferably, in step (4), the vacuum condition includes: an absolute pressure not higher than 10Pa, preferably 0-5Pa.

[0064] The present invention has a wide range of selection for the specific type of the iron salt, which can be selected from soluble organic or inorganic salts of iron, for example, at least one of ferric nitrate, ferric chloride and ferric citrate ammonium, preferably ferric nitrate.

[0065] Preferably, the concentration of the iron salt solution is 0.05-0.5 mol / L, preferably 0.2-0.5 mol / L.

[0066] Preferably, the impregnation is carried out under stirring conditions, and the impregnation time is 0.5-5h.

[0067] According to some preferred embodiments of the present invention, the amount of the iron salt and the nitrogen-oxygen co-doped carbon nanocage is such that, as measured by X-ray photoelectron spectroscopy, the molar content of carbon in the composite material is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%; preferably, as measured by X-ray photoelectron spectroscopy, the molar content of carbon in the composite material is 84-94%, the molar content of oxygen is 5-8%, the molar content of nitrogen is 0.5-3%, and the molar content of iron is 0.5-5%.

[0068] According to some preferred embodiments of the present invention, the preparation method further comprises: subjecting the impregnated product to solid-liquid separation, washing and drying, and then subjecting the heat treatment to the solid-liquid separation and washing to remove the residual iron salt solution on the surface of the carrier. The present invention has no particular limitation on the specific operation and conditions of the solid-liquid separation and washing, and the solid-liquid separation and washing can be carried out by conventional methods in the art. For example, the solid-liquid separation can be carried out by filtering. Preferably, the washing can use water and / or alcohol as a detergent.

[0069] According to the present invention, preferably, the drying is performed by freeze drying. Preferably, the freeze drying temperature is -40 to -10°C and the time is 12-48 hours.

[0070] According to some preferred embodiments of the present invention, the heat treatment is carried out under an inert atmosphere, and the conditions of the heat treatment include: a temperature of 300-600°C, preferably 300-400°C; a time of 2-6h, preferably 2-4h. The inert atmosphere has the same definition as in step (2), for example, it can be argon.

[0071] According to the present invention, in step (5), the passivation treatment conditions include: temperature of 20-40°C and time of 0.5-2h. The passivation treatment is beneficial to further improve the stability of the material and prevent the material from spontaneously igniting when it suddenly contacts with air when it is taken out.

[0072] In the present invention, the oxygen-containing atmosphere may be a mixed gas of oxygen and an inert gas, and the volume content of oxygen in the oxygen-containing atmosphere is 1-3%.

[0073] According to some preferred embodiments of the present invention, the preparation method further comprises: subjecting the product obtained by the passivation treatment to a second pickling and drying. The second pickling is used to remove iron oxides on the surface of the product of the passivation treatment. The specific operation process of the second pickling can adopt the existing technology known to those skilled in the art, and the present invention has no special limitation on this.

[0074] The second pickling can be carried out with an acid or an acid aqueous solution conventional in the art, and can be the same or different from the pickling agent in the pickling in step (2), as long as the iron oxide on the surface of the passivated product can be removed. Preferably, the second pickling is carried out with a nitric acid aqueous solution, and the concentration of the nitric acid aqueous solution is preferably 0.5-2 mol / L. The present invention does not particularly limit the amount of the pickling agent, as long as the above purpose can be achieved, and those skilled in the art can choose according to actual conditions.

[0075] The second pickling may be optionally repeated. Preferably, the second pickling is repeated 1-2 times.

[0076] Preferably, the drying conditions include: temperature of 60-120° C. and time of 8-24 h.

[0077] The third aspect of the present invention provides application of the composite material in a metal lithium battery.

[0078] The negative electrode active material of the metal lithium battery can be the composite material, or can include the composite material and optionally a conventional negative electrode material in the art, and the present invention has no particular limitation on this. As long as the negative electrode active material contains the composite material of the present invention, the overpotential of the lithium metal deposition reaction occurring at the lithium metal negative electrode during the charge and discharge process can be reduced, thereby facilitating the optimization of lithium deposition and improving the cycle performance of the metal lithium battery.

[0079] The present invention has no particular limitation on the composition and structure of the metal lithium battery. The metal lithium battery may further include a positive electrode, a separator, an electrolyte, etc., which can all be conventionally selected in the art and are well known to those skilled in the art.

[0080] The present invention will be described in detail below through examples.

[0081] In the present invention, room temperature refers to 25±5°C.

[0082] The surface morphology of the material was characterized by high-resolution transmission electron microscopy (HRTEM). The model of the high-resolution transmission electron microscope used was JEM-2100 (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope were: the acceleration voltage was 200 kV.

[0083] The composition and valence state changes of each element on the surface of the material were determined by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy analysis was carried out on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific. The excitation source was monochromatic Al Kα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis was 6.5×10 -10 The electron binding energy was calibrated with the C1s peak (284.3 eV) of elemental carbon. The data were processed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module.

[0084] The model of the XRD diffractometer used in the present invention is an XRD-6000 X-ray powder diffractometer (Shimadzu, Japan), and the XRD test conditions are: Cu target, Kα ray (wavelength λ=0.154nm), tube voltage of 40kV, tube current of 200mA, and scanning speed of 10°(2θ) / min.

[0085] Example 1

[0086] (1) Weigh 14.67 g of basic nickel carbonate and 20.46 g of ethylenediaminetetraacetic acid (EDTA), add them into a beaker containing 100 mL of deionized water, stir at 80° C. to obtain a homogeneous solution, and continue heating and evaporating to obtain a solid precursor.

[0087] (2) placing the precursor obtained in step (1) in a porcelain boat, and then placing the porcelain boat in the constant temperature zone of a tubular furnace for low-temperature pyrolysis, introducing nitrogen at a flow rate of 80 mL / min, and heating to 350°C at a rate of 5°C / min. After keeping the temperature constant for 2 hours, stopping heating, and cooling to room temperature under a nitrogen atmosphere to obtain a pyrolysis product.

[0088] (3) The pyrolysis product obtained in step (2) was added to an aqueous solution containing 0.5M hydrochloric acid and stirred at 90°C for 4 hours for acid washing, then filtered, washed with deionized water until the filtrate was neutral, and then the filter cake was dried in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-oxygen co-doped carbon nanocages. The specific surface area of ​​the nitrogen-oxygen co-doped carbon nanocages was 480 m 2 / g, and the pore volume of the cage wall is 0.77cm 3 / g.

[0089] (4) Weigh 2g of carbon nanocages and add them to a two-necked flask, connect a 250mL dropping funnel, add 80mL of 0.5mol / L ferric nitrate aqueous solution to the dropping funnel; connect a piston joint for vacuuming to the other port of the two-necked flask, and connect a vacuum pump. Evacuate the two-necked flask to below 10Pa, close the piston joint, open the dropping funnel, and quickly add the ferric nitrate solution to the two-necked flask. After stirring for 2h, filter the mixed liquid, and place the filter cake in a freeze dryer at -10℃ and dry for 24h. Grind the dried sample and place it in a tubular furnace, calcine at 350℃ for 2h in an argon gas flow of 500mL / min, and cool to room temperature.

[0090] (5) At room temperature, the product obtained in step (4) was passivated in a 1 vol% O2 / Ar atmosphere for 0.5 h.

[0091] (6) The product obtained in step (5) was added into a 250 mL beaker, and 80 mL of 0.5 mol / L dilute nitric acid was added for washing. The washing with dilute nitric acid was repeated once to remove excess iron oxide particles on the surface, and then washed with deionized water until neutral. The product was placed in a forced air drying oven at 80° C. and dried for 2 h. The obtained composite material was recorded as A1.

[0092] The XRD characteristics of composite material A1 are as follows: Figure 1 As shown, by comparing with the standard card, it can be seen that the product has carbon and Fe2O3 with graphite structure.

[0093] The XPS picture of this material is as follows Figure 2 As shown in the figure, it can be seen that in addition to carbon, the material also contains oxygen, nitrogen and iron. The atomic percentage of each element is: carbon is 91.56%, oxygen is 6.21%, nitrogen is 0.78%, and iron is 1.45%. The molar ratio of oxygen to nitrogen is 8:1.

[0094] The XPS spectrum of Fe 2p obtained by peak separation software is as follows: Figure 3 As shown, it can be seen that the iron element mainly exists in the form of Fe2O3.

[0095] The TEM image of this material is shown in Figure 4 As shown, it can be seen that the material contains many carbon cage units containing Fe2O3, each unit is in the shape of a hollow cage, and clear Fe2O3 lattice stripes can be seen in the cage, indicating that Fe2O3 is contained in the cage. At the same time, it can be obtained from the TEM image measurement that the particle diameter of the composite material A1 is about 5-20nm, the thickness of the cage wall of the nitrogen-oxygen co-doped carbon nanocage is 2nm, and the carbon cage has obvious graphite carbon lattice stripes.

[0096] Example 2

[0097] (1) Weigh 14.67 g of basic nickel carbonate and 20.46 g of ethylenediaminetetraacetic acid (EDTA), add them into a beaker containing 100 mL of deionized water, stir at 80° C. to obtain a homogeneous solution, and continue heating and evaporating to obtain a solid precursor.

[0098] (2) placing the precursor obtained in step (1) in a porcelain boat, and then placing the porcelain boat in the constant temperature zone of a tubular furnace for low-temperature pyrolysis, introducing nitrogen at a flow rate of 80 mL / min, and heating to 400°C at a rate of 8°C / min. After maintaining the constant temperature for 3 hours, stopping heating, and cooling to room temperature under a nitrogen atmosphere to obtain a pyrolysis product.

[0099] (3) The pyrolysis product obtained in step (2) was added to an aqueous solution containing 1.5M hydrochloric acid and stirred at 60°C for 8h for acid washing, then filtered, washed with deionized water until the filtrate was neutral, and then the filter cake was dried in a constant temperature oven at 120°C for 6h to obtain nitrogen-oxygen co-doped carbon nanocages. The specific surface area of ​​the nitrogen-oxygen co-doped carbon nanocages was 450m 2 / g, and the pore volume of the cage wall is 0.76cm 3 / g.

[0100] (4) Weigh 2g of carbon nanocages and add them to a two-necked flask. Connect a 250mL dropping funnel and add 80mL of 0.5mol / L ferric nitrate aqueous solution to the dropping funnel. Connect a piston joint for vacuuming to the other port of the two-necked flask and connect it to a vacuum pump. Vacuum the two-necked flask to below 10Pa, close the piston joint, open the dropping funnel, and quickly add the ferric nitrate solution to the two-necked flask. After stirring for 2h, filter the mixed liquid and dry the filter cake in a freeze dryer at -10℃ for 24h. Grind the dried sample and place it in a tubular furnace. Calcined at 400℃ for 3h in an argon gas flow of 500mL / min and cooled to room temperature.

[0101] (5) The product obtained in step (4) was passivated with 1 vol% O2 / Ar for 0.5 h to obtain a composite material denoted as A2. Figure 1 Similar to the characteristic peaks of carbon and Fe2O3 with graphite structure, the morphology of composite material A2 was characterized by TEM, which is consistent with Figure 4 Similarly, the particles are in the shape of hollow cages, and clear Fe2O3 lattice fringes can be seen inside the cages, indicating that Fe2O3 is contained in the cages. At the same time, the TEM image shows that the particle diameter of the composite material A2 is about 5-20nm, and the thickness of the cage wall of the nitrogen-oxygen co-doped carbon nanocage is 1.6nm.

[0102] XPS measured the atomic percentage of each element in the composite material as follows: carbon element is 92.71%, oxygen element is 5.32%, nitrogen element is 0.82%, iron element is 1.15%, and the molar ratio of oxygen to nitrogen is 6.5:1.

[0103] Example 3

[0104] (1) Weigh 14.67 g of basic nickel carbonate and 20.46 g of ethylenediaminetetraacetic acid (EDTA), add them into a beaker containing 100 mL of deionized water, stir at 80° C. to obtain a homogeneous solution, and continue heating and evaporating to obtain a solid precursor.

[0105] (2) placing the precursor obtained in step (1) in a porcelain boat, and then placing the porcelain boat in the constant temperature zone of a tubular furnace for low-temperature pyrolysis, introducing nitrogen at a flow rate of 80 mL / min, and heating to 650°C at a rate of 10°C / min. After keeping the temperature constant for 2 hours, stopping heating, and cooling to room temperature under a nitrogen atmosphere to obtain a pyrolysis product.

[0106] (3) The pyrolysis product obtained in step (2) was added to an aqueous solution containing 1M hydrochloric acid and stirred at 90°C for 4 hours for acid washing, then filtered, washed with deionized water until the filtrate was neutral, and then the filter cake was dried in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-oxygen co-doped carbon nanocages. The specific surface area of ​​the nitrogen-oxygen co-doped carbon nanocages was 348 m 2 / g, and the pore volume of the cage wall is 0.82cm 3 / g.

[0107] (4) Weigh 2g of carbon nanocages and add them to a two-necked flask, connect a 250mL dropping funnel, add 80mL of 0.5mol / L ferric nitrate aqueous solution to the dropping funnel; connect a piston joint for vacuuming to the other port of the two-necked flask, and connect a vacuum pump. Evacuate the two-necked flask to below 10Pa, close the piston joint, open the dropping funnel, and quickly add the ferric nitrate solution to the two-necked flask. After stirring for 2h, filter the mixed liquid and put the filter cake into a freeze dryer at -10℃ and dry for 24h. Grind the dried sample and put it into a tubular furnace, calcine it at 350℃ for 2h in an argon gas flow of 500mL / min, and cool it to room temperature.

[0108] (5) The product obtained in step (4) was passivated with 1% O2 / Ar for 0.5 h to obtain a composite material denoted as A3. At the same time, it can be obtained from TEM images that the particle diameter of the composite material A2 is about 5-20 nm, and the thickness of the cage wall of the nitrogen-oxygen co-doped carbon nanocage is 1.5 nm.

[0109] (6) The calcined sample was added into a 250 mL beaker and washed with 80 mL of 0.5 mol / L dilute nitric acid. The sample was washed with dilute nitric acid once to remove excess iron oxide particles on the surface. The sample was then washed with deionized water until neutral and dried in a forced air drying oven at 80 °C for 2 h. The obtained composite material was recorded as A3.

[0110] XPS measured the atomic percentage of each element in the composite material as follows: carbon element is 95.2%, oxygen element is 2.65%, nitrogen element is 0.95%, iron element is 1.2%, and the molar ratio of oxygen to nitrogen is 2.8:1.

[0111] Example 4

[0112] The method of Example 1 is followed, except that the concentration of the ferric nitrate aqueous solution is 5 mol / L.

[0113] The obtained composite material was recorded as A4.

[0114] XPS measured the atomic percentage of each element in the composite material as follows: carbon element is 87.33%, oxygen element is 5.92%, nitrogen element is 0.73%, iron element is 6.02%, and the molar ratio of oxygen to nitrogen is 8.1:1.

[0115] Comparative Example 1

[0116] The method of Example 1 is followed, except that step (4) is as follows: weigh 0.14 g of ferric citrate ammonium and dissolve it in 10 mL of aqueous solution. Slowly add 0.3 g of carbon nanocages into 10 mL of deionized water, fully disperse, mix with the solution of ferric citrate ammonium, soak for 6 hours, pour the mixture into a PTFE beaker, and blow dry at 80°C for 10 hours. The dried sample is placed in a tubular furnace protected by Ar atmosphere, the tubular furnace is evacuated for 5 minutes, filled with Ar gas, and the evacuation and filling are repeated three times to remove the air in the tubular furnace. In an Ar gas flow of 60 mL / min, the temperature is raised to 350°C at a heating rate of 10°C / min, and then the mixture is kept at a constant temperature for 2 hours, and then naturally cooled to room temperature.

[0117] Then, the passivation treatment was performed according to the method of Example 1, and the obtained product was recorded as composite material DA1.

[0118] XPS measured the atomic percentage of each element in the composite material as follows: carbon element is 91.97%, oxygen element is 6.23%, nitrogen element is 0.76%, and iron element is 1.04%. The molar ratio of oxygen to nitrogen is 8.2:1. TEM characterization showed that the ferric oxide in the composite material was loaded on the surface of the carbon cage and did not enter the carbon cage.

[0119] Comparative Example 2

[0120] A nitrogen-doped carbon-coated iron oxide negative electrode material Fe2O3@C was prepared according to the method of Example 1 of CN106816595A, and was denoted as composite material DA2. Characterization by SEM and TEM showed that the thickness of the nitrogen-doped carbon layer of the composite material was about 30 nm.

[0121] Test example:

[0122] S1. Grind the composite material and the conductive agent Super-P in a mortar for 15 minutes. After grinding evenly, add the NMP solution of the binder PVDF (mass fraction 5%) in proportion. The mass ratio of the composite material, the conductive agent and the binder is 8:1:1. Stir on a magnetic stirrer for 6 hours; evenly apply the obtained paste slurry on a 9μm thick current collector copper foil with a coating thickness of 75μm; then dry it in a vacuum drying oven at 60℃ for 20 hours for use. The dried electrodes are respectively made into circular pole pieces with a diameter of 12mm; and maintained at a pressure of 8MPa for 30-180 seconds.

[0123] S2. Use metallic lithium as the negative electrode, Celgard membrane as the separator, select 1 mol / L lithium bis(trifluoromethylsulfonyl)imide as the electrolyte, 1% lithium nitrate as the additive, and the solvent volume ratio DOL (1,3-dioxolane): DME (ethylene glycol dimethyl ether) = 1:1 to assemble into a CR2032 button battery.

[0124] S3, use the LAND CT2001A charge and discharge instrument of Wuhan Lanbo Electronics Co., Ltd. to carry out charge and discharge test, the conditions are: current density is 0.5mA / cm 2 , the time is 10h, and the obtained lithium deposition overpotential is shown in Table 1.

[0125] Table 1

[0126] Example No. Lithium deposition overpotential mV Example 1 11 Example 2 13 Example 3 17 Example 4 18 Comparative Example 1 45 Comparative Example 2 40

[0127] Combined with the results in Table 1, it can be seen from the comparison of the embodiment and the comparative example that the composite material prepared by the present invention uses nitrogen-oxygen co-doped carbon nanocage as a carrier, and the carbon cage is loaded with ferric oxide, and the lithium deposition overpotential is greatly reduced, indicating that the material has good lithium affinity and can achieve confined directional growth of metallic lithium. Preferably, by further controlling the content of ferric oxide and the nitrogen and oxygen content in the nitrogen-oxygen co-doped carbon nanocage, it is beneficial to further reduce the lithium deposition overpotential to below 15mV.

[0128] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite material, characterized in that: The composite material comprises a carrier and Fe2O3 nanoparticles filled in the carrier, wherein the carrier is a nitrogen-oxygen co-doped carbon nanocage; The X-ray photoelectron spectroscopy measured that the molar content of carbon in the composite material was 75-98%, the molar content of oxygen was 1-10%, the molar content of nitrogen was 0.5-5%, and the molar content of iron was 0.5-10%.

2. The composite material according to claim 1, wherein The molar content of carbon in the composite material measured by X-ray photoelectron spectroscopy is 84-94%, the molar content of oxygen is 5-8%, the molar content of nitrogen is 0.5-3%, and the molar content of iron is 0.5-5%; Preferably, in the composite material, the molar ratio of oxygen to nitrogen is 5-15:1, preferably 5-10:

1.

3. The composite material according to claim 1 or 2, wherein: The particle diameter of the composite material is 5-40 nm, preferably 5-30 nm, more preferably 5-20 nm; And / or, the thickness of the cage wall of the nitrogen and oxygen co-doped carbon nanocage in the composite material is 1-30 nm, preferably 1-10 nm, and more preferably 1-5 nm.

4. The composite material according to any one of claims 1 to 3, wherein: The specific surface area of ​​the nitrogen and oxygen co-doped carbon nanocage is 50-1000m 2 / g, preferably 200-800m 2 / g, more preferably 300-600m 2 / g; And / or, the pore volume of the cage wall of the nitrogen and oxygen co-doped carbon nanotubes is 0.5-1cm 3 / g, preferably 0.65-1cm 3 / g.

5. A method for preparing a composite material, comprising the following steps: (1) providing a homogeneous solution containing a transition metal salt, a nitrogen-containing organic carboxylic acid and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid; and the mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.1-100; (2) subjecting the precursor to low-temperature pyrolysis in an inert atmosphere and / or a reducing atmosphere to obtain a pyrolysis product; the temperature of the low-temperature pyrolysis is not higher than 650° C.; (3) acid-washing the pyrolysis product, and then performing solid-liquid separation, washing and drying to obtain nitrogen-oxygen co-doped carbon nanocages; (4) impregnating the nitrogen-oxygen co-doped carbon nanocage with an iron salt solution under vacuum conditions, and then performing a heat treatment; (5) Under an oxygen-containing atmosphere, the product obtained in step (4) is passivated.

6. The preparation method according to claim 5, wherein: The mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.5-50, preferably 1:0.5-5; And / or, the transition metal salt is selected from organic acid salts and / or inorganic salts of transition metals; preferably, the organic acid salt of transition metals is an organic carboxylate salt containing no heteroatoms, preferably an acetate; preferably, the inorganic salt of transition metals is at least one of transition metal halides, carbonates and basic carbonates; and / or, the transition metal is a Group VIII metal and / or a Group IB metal, preferably at least one of iron, cobalt, nickel and copper, more preferably nickel; And / or, the solvent is ethanol and / or water.

7. The preparation method according to claim 5 or 6, wherein: In step (2), the low-temperature pyrolysis conditions include: a heating rate of 0.5-30°C / min, preferably 1-10°C / min; a temperature of 350-450°C, preferably 350-400°C; a constant temperature time of 20-600min, preferably 60-480min; and / or, the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium; And / or, the reducing atmosphere is hydrogen.

8. The preparation method according to any one of claims 5 to 7, wherein: In step (3), the acid washing removes the transition metals in the pyrolysis product to form a hollow cage-like structure; Preferably, the pickling agent used for pickling the pyrolysis product is an inorganic acid aqueous solution and / or an organic acid aqueous solution, preferably at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a nitric acid aqueous solution and a citric acid aqueous solution, more preferably a hydrochloric acid aqueous solution; And / or, the concentration of the inorganic acid aqueous solution or the organic acid aqueous solution is 0.5-2 mol / L; And / or, in step (3), the pickling temperature is 20-110°C, preferably 60-90°C; the time is 0.1-48h, preferably 4-12h.

9. The preparation method according to any one of claims 5 to 8, wherein: In step (4), the vacuum conditions include: an absolute pressure not higher than 10 Pa; And / or, the concentration of the iron salt solution is 0.05-0.5 mol / L; And / or, the iron salt is at least one of ferric nitrate, ferric chloride and ferric ammonium citrate; And / or, the amount of the iron salt and the nitrogen-oxygen co-doped carbon nanocage is such that, as measured by X-ray photoelectron spectroscopy, the molar content of carbon in the composite material is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%; And / or, the heat treatment is performed under an inert atmosphere, and the conditions of the heat treatment include: a temperature of 300-600° C. and a time of 2-4 hours.

10. The preparation method according to any one of claims 5 to 9, wherein: In step (5), the passivation treatment conditions include: temperature of 20-30°C and time of 0.5-2h; Preferably, the volume content of oxygen in the oxygen-containing atmosphere is 1-3%.

11. Use of the composite material according to any one of claims 1 to 4 or the composite material prepared by the preparation method according to any one of claims 5 to 10 in metal lithium batteries.

Citation Information

Patent Citations

  • Metal oxide composite material and preparation method and application thereof

    CN113540456A

  • Negative electrode material, negative electrode sheet, electrochemical device, and electronic device

    CN114270574A

  • Nitrogen-doped nano carbon cage as well as preparation method and application thereof

    CN115966714A

  • Nitrogen-doped nano carbon material and preparation method thereof, metal lithium negative electrode and preparation method thereof, and metal lithium battery

    CN116031405A

  • Carbon-based catalyst containing metal platinum as well as preparation method and application of carbon-based catalyst

    CN116706104A